Between activism and the academy: The urban as political terrain. (August 2015) - Oldfield, Sophie
A growing consensus suggests that urban scholarship can benefit from engaging with knowledge in multiple sites in and beyond the academy, for instance with activism central to politics in cities worldwide. This paper explores narratives of urban politics produced with activists to reflect on how we account for knowledge and practice in theorising the urban as political terrain. Research conducted with activists in a community-based 'Civic' organisation in Cape Town, South Africa highlights the everyday toil that shapes resistance and its politics, the frictions and engagements behind protest headlines. In opening up theorisations of activism and revolution to the knowledge practices of movements, the paper argues we may more cogently take account of the strategic and intimate politics that characterise contemporary activism, and reshape notions of 'revolution', urban politics and research practice in contemporary cities, a project broadly relevant in the Global South and North.